Relationship Between Hypertension During Pregnancy And Early Ruptured Membranes With Neonatory Asphicia At Home Full Bethesda General Illness - Indra Riris Delima; Eva Hotmaria; Ronni Naudur Siregar; Agnes; Mutiara Hutasoit (TOUR HEALTH JOURNAL, 2022)
Purpose: This study aims to analyze hypertension during pregnancy and premature rupture of membranes (PROM) with the incidence of neonatorium asphyxia at R. Method: This type of research is analytic observational research using a case-control research design. The population in this study were all mothers who had just given birth to a baby at RSU Full Betesda  for the period January-December 2021, totaling 284 people with a sample consisting of 37 samples for the case group and 37 samples for the control group. Collecting data with secondary data and analyzed with the chi Square statistical test with a confidence level of 95%. Results: The results showed that there was a relationship between hypertension during pregnancy and the incidence of neonatorium asphyxia at RSU Full Betesda  and there was a relationship between premature rupture of membranes and neonatal asphyxia at RSU Full Betesda. Discussion and Conclusion:  It is suggested to RSU Full Betesda  to improve human resources by providing training on the management of hypertension during pregnancy and premature rupture of membranes, so that service providers, especially midwives, can handle emergencies properly, thereby reducing complications from their actions and for midwives in order to provide more health services. based on professional standards in providing comprehensive midwifery care services and can improve abilities, skills so that the handling of newborns with asphyxia is adequate.